BILANGAN DOMINASI EKSENTRIK TERHUBUNG pada GRAF - Tito Sumarsono (Jurnal Matematika, 2016)
ABSTRACT. Given a graph  , comprising a set   of vertices and a set   of edges. A set   is a dominating set of , if every vertex in  is adjacent to at least one vertex in . The cardinality of minimum dominating set of  it’s domination number and is denoted by . A set  is a eccentric dominating set if  is an dominating set of  and for every  in  there exist at least one eccentric point of  in . The cardinality of minimum eccentric dominating set of  it’s eccentric domination number and is denoted by . A set  is a connected eccentric dominating set if  is an eccentric dominating set of  and the induced subgraph  is connected. The cardinality of minimum connected eccentric dominating set of  it’s connected eccentric domination number and is denoted by . In this paper we discuss connected eccentric dominating set and connected eccentric domination number on special graphs which are complete graph, star graph, complete bipartite graph, cycel graph and wheel graph.  Keywords : eccentric dominating set, eccentric domination number, connected   eccentric dominating set, connected eccentric domination number